Development of a computer-based learning environment in the conditions of multicultural education in the European Union (Educational Dimension, 2020)
In the article, based on the results of the analysis of scientific and pedagogical works of domestic and foreign scientists, the concept of multicultural competence of the student and the concept of computer-oriented learning environment in the conditions of multicultural education of students are specified. The scientific search on the basis of the analysis of government documents, programs and projects of informatization of the educational environment of the European Union and the Council of Europe made it possible to identify the main stages of the development of a computer-oriented learning environment in the conditions of multicultural education of students in the EU countries: information and preparation (1997–2000); infrastructural and provisional (2001–2004), pedagogically communicative (2004–2006), project provisional (2007–2010), competently oriented (2010–2013), project activity (2014 — present and time).